Analisis Kinerja Sistem Informasi dengan Metode End-User Computing Satisfaction (Studi Kasus pada PT PLN Langsa) - Roy Sari Milda Siregar (Jurnal Optimalisasi, 2016)
This evaluation is crucial to develop a better understanding on whether the new Information System is applicable in supporting the staff duties and work responsibilities. This present study is aimed at evaluating the performance of the Information System based on the end-user’s point of view. This research is a descriptive-quantitative field study. In the data analysis, the framework of End-User Computing Satisfaction (EUCS) was used to the primary user-level which consist of five variables, namely, Content, Accuracy, Format, Ease of Use and Timeliness and an additional variabel, satisfaction. A total of 39 questionnaires were distributed to operators in PT PLN Langsa. Based on the analysis, the satisfaction rate as per the EUCS are as follows: low at 25.6%, medium at 56.64% and high at 18%. The percentage of user satisfaction to the information sistem is at 72,9% from the expected rate.Keywords: End-user computing satisfaction, user satisfaction, evaluation of information systems.